2007
DOI: 10.1074/jbc.m608266200
|View full text |Cite
|
Sign up to set email alerts
|

Unique Ability of Activated CD4+ T Cells but Not Rested Effectors to Migrate to Non-lymphoid Sites in the Absence of Inflammation

Abstract: Recent studies suggest that effector T cells generated by immune responses migrate to multiple non-lymphoid sites, even those without apparent expression of antigen or inflammation. To investigate the ability of distinct CD4؉ T lymphocyte subsets to enter and persist in non-lymphoid, noninflamed compartments, we examined the migration and persistence of naïve, effector, and rested effector CD4؉ T cells generated in vitro following transfer to nonimmunized adoptive hosts. Th1 and Th2 effectors migrated to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…We have previously shown that only the most activated and differentiated donor CD4 T cells migrate to the lung during the peak of the primary flu infection [70]. This cohort of responding cells also resembles 4-day in vitro generated Th1-polarized effectors, both in terms of phenotype and cytokine production (IFNc high , IL-2 low ), and we have also shown that only highly activated in vitro-generated effectors migrate to the lung [71]. After viral clearance, about day 9-10 post-infection, numbers of donor cells in the lung fall dramatically (Fig.…”
Section: Rapid Transition From Effector To Memory In Vivosupporting
confidence: 62%
See 1 more Smart Citation
“…We have previously shown that only the most activated and differentiated donor CD4 T cells migrate to the lung during the peak of the primary flu infection [70]. This cohort of responding cells also resembles 4-day in vitro generated Th1-polarized effectors, both in terms of phenotype and cytokine production (IFNc high , IL-2 low ), and we have also shown that only highly activated in vitro-generated effectors migrate to the lung [71]. After viral clearance, about day 9-10 post-infection, numbers of donor cells in the lung fall dramatically (Fig.…”
Section: Rapid Transition From Effector To Memory In Vivosupporting
confidence: 62%
“…For example, memory CD4 T cells may influence various APC, B cells, and CD8 T cells via the rapid production of large amounts of Th1-or Th2-polarized cytokines as well as IL-2. However, other important properties, such as migration to non-lymphoid tissues, are only evident after memory cells re-expand into highly activated cells (memory or secondary effectors) [71]. Thus, re-activated memory CD4 T cells can also impact later phases of protective responses with similar kinetics as primary effectors arising from naïve precursors.…”
Section: Primary Versus Secondary Cd4 Effectorsmentioning
confidence: 99%
“…Even though the adaptive immune response is initiated in the local lymph nodes and thereafter effectors migrate to the site of infection [33][34][35][36], it is important to establish this proposition in the present study as well, because immunity of the lungs plays a seminal role in imparting protection against M. tuberculosis. Consequently, we next studied the status of T cell memory in the lungs.…”
Section: Discussionmentioning
confidence: 97%
“…33 (Figures 1A-1C). Furthermore, compared with those isolated from the BCG groups, lymphocytes isolated from mice in the BCG7.15 groups showed significantly higher production levels of IFN-g ( ) ( Figure 1D).…”
Section: Bcg Coadministered With Il-7 and Il-15 Augments Lymphoprolifmentioning
confidence: 99%
“…Discussion Naïve CD4 T cells generally have been considered to reside principally within the secondary lymphoid organs, including the lymph nodes and spleen, and to be largely excluded from nonlymphoid tissues (8), although some reports have indicated that CD4 and CD8 T cells with a naïve phenotype can be found in such tissues (10,41). In contrast, memory and effector cells can gain access to nonlymphoid organs, where they can provoke immediate responses when confronted with their cognate antigens under appropriate conditions (42)(43)(44). In the present study, we found that the majority of CD4 T cells extracted from the lungs had a naïve phenotype.…”
Section: Mediastinal Lymph Node Cells Entering In a Cd62l-independentmentioning
confidence: 99%